Production, purification and characterization pediocin from Pediococcus acidilactici locally isolated (Damascus University Journal of agriculture sciences, 2024)
This study was conducted at Food Science Department, Faculty of Agriculture, Damascus University and directorate of internal trade and consumer protection laboratory in Damascus in 2021. The research aimed to produce pediocin by Pediococcus acidilactici isolated from some food products traditionally manufactured and determine its effectiveness in inhibiting some types of spoilage bacteria. Production was carried out by growing in MRS broth medium, then extraction and purification, and then measuring its effectiveness in inhibiting some types of spoilage bacteria previously isolated. Pediocin efficiency then tested against heat treatments, pH changes and protease enzymes. The results showed a good efficacy ofpediocin in inhibiting the studied bacteria, which are Proteus mirabilis, Citrobacter murliniae, Escherichia coli, Pseudomonas spp., Listeria monocytogenes and with a lesser degree Klebsiela oxytoca. The results also showed the stability of pediocin toward the heat treatments up to 100°C for 15 minutes, and an improvement in the inhibitory activity in alkaline media and a decrease in this activity in acidic media to reach the lowest level at pH=11. The inhibitory activity of pediocin significantly reduced when treated with protease enzymes.
Keywords: Pediocin; Spoilage Bacteria; Heat Treatments; Ph